1988
DOI: 10.1038/336254a0
|View full text |Cite
|
Sign up to set email alerts
|

Transient association of newly synthesized unfolded proteins with the heat-shock GroEL protein

Abstract: It has been suggested that newly synthesized proteins are maintained in their unfolded state by cellular ATP-driven factors which may prevent or reverse the formation of misfolded structures or promote the correct assembly of oligomeric proteins or post-translational secretion. Using a photocross-linking approach, we have identified the 20S heat-shock GroEL protein as the major cytosolic component which forms a complex with the unfolded newly synthesized pre-beta-lactamase or chloramphenicol acetyltransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
188
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(194 citation statements)
references
References 23 publications
5
188
1
Order By: Relevance
“…ATP is apparently not necessary for association of the precursor proteins with GroEL. The complexes dissociate after adding ATP (BOCHKAREVA et al 1988). Since the interaction of GroEL and GroES was only observed in the presence of ATP (CHANDRASEKHAR et al 1986), a role of the GroES protein in the release of GroEL-associated proteins was assumed (KUSUKAWAet al 1989).…”
Section: Translocation Of Proteins Across Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…ATP is apparently not necessary for association of the precursor proteins with GroEL. The complexes dissociate after adding ATP (BOCHKAREVA et al 1988). Since the interaction of GroEL and GroES was only observed in the presence of ATP (CHANDRASEKHAR et al 1986), a role of the GroES protein in the release of GroEL-associated proteins was assumed (KUSUKAWAet al 1989).…”
Section: Translocation Of Proteins Across Membranesmentioning
confidence: 99%
“…Evidence for interaction of GroEL with newly synthesized proteins came from photo-cross-linking experiments (BOCHKAREVA et al 1988). After such cross-linking newly synthesized, plasmid-encoded secretory ^-lactamase (and plasmid-encoded chloramphenicol acetyltransferase) sedimented during ultracentrifugation as a 20S particle.…”
Section: Translocation Of Proteins Across Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bochkareva et al (6) showed that GroEL interacts specifically with the immature forms of ,-lactamase and chloramphenicol acetyltransferase, befitting a chaperonin. The dissociation of this complex was again dependent on the presence of ATP.…”
mentioning
confidence: 99%
“…In particular, one class of chaperones (typified by GroEL in prokaryotes) consist of multisubunit toroidal ring assemblies and are believed to function by providing a sequestered environment in which aberrant folding and aggregation are prevented; the correctly folded polypeptide is ultimately discharged in an Mg-ATP-dependent reaction. These toroidal structures are termed chaperonins (6,10,19,28,34,35,46). Actin and tubulin are the major soluble cytoplasmic proteins in eukaryotic cells and are the subunits from which actin filaments and microtubules are assembled.…”
mentioning
confidence: 99%